Maintenance of Synaptic Stability Requires Calcium-Independent Phospholipase A2 Activity - Julie Allyson; Xiaoning Bi; Michel Baudry; Guy Massicotte (Neural Plasticity)
Phospholipases A2 (PLA2s) represent one of the largest groups of lipid-modifying enzymes. Over the years, significant advances have been made in understanding their potential physiological and pathological functions. Depending on their calcium requirement for activation, PLA2s are classified into calcium dependent and independent. This paper mainly focuses on brain calcium-independent PLA2 (iPLA2) and on the mechanisms by which they influence neuronal function and regulate synaptic plasticity. Particular attention will be given to the iPLA2γ isoform and its role in the regulation of synaptic glutamate receptors. In particular, the paper discusses the possibility that brain iPLA2γ deficiencies could destabilise normal synaptic operation and might contribute to the aetiology of some brain disorders. In this line, the paper presents new data indicating that iPLA2γ deficiencies accentuate AMPA receptor destabilization and tau phosphorylation, which suggests that this iPLA2 isoform should be considered as a potential target for the treatment of Tau-related disorders.